Detection of antibodies against bovine respiratory syncytial virus (BRSV) in dairy cattle with different prevalences of bovine herpesvirus type 1 (BoHV-1) in São Paulo State, Brazil - Affonso, Ingrid Bortolin [UNESP]; Gatti, Sandra Possebon [UNESP]; Alexandrino, Bruna [UNESP]; Oliveira, Monica Costa [UNESP]; Ramos de Medeiros, Andrea Souza [UNESP]; Buzinaro, Maria da Gloria [UNESP]; Samara, Samir Issa [UNESP] (Universidade Estadual de Londrina (UEL), 2011)
Serum samples from three dairy farms classified as high (1, 78.6%), medium (2, 40.0%) and low (3, 1.6%) prevalence for bovine herpesvirus type 1 (BoHV-1) from São Paulo State, were collected to analyze the prevalence to the bovine respiratory syncytial virus (BRSV) by virus neutralization test. The BRSV observed prevalences for farms 1, 2, and 3 were 45.61%, 84.42%, and 54.09%, respectively. Farm 2 showed higher prevalence to BRSV (P < 0.0001) than farms 1 and 3, which were equivalent (P = 0.2291). Two risk factors, herd size and milder climate conditions, were associated to BRSV. The prevalence of BRSV in farm 1 was statistically lower than BoHV-1 prevalence (P < 0.0001). on the other side, farms 2 and 3 have prevalences of BRSV higher than of BoHV-1 (P < 0.0001 in both comparisons). We may conclude, at least for the studied farms, that BRSV and BoHV-1 did not interact and the differences observed between BRSV and BoHV-1 prevalences into each herd did not have epidemiological importance.
Keywords: Bovine respiratory syncytial virus; Bovine herpesvirus type 1; Prevalence; virus neutralization test; Brazil